Comparative analysis of relation between premorbid period and variants of endogenous mental disorders beginning - A. A. Krasnov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
Based on the long-term observation period (1986 through 2012) the properties of endogenous mental disorders premorbid period in 107 persons (of mean age 21.5±1.5 years) were studied. In 41.2% of the cases, premorbid period was characterized by premorbid disorders, which included disorders of development, deviation of behavior and motor skills, behavioral abnormalities, affective and somatic disorders combined with quantitative changes in personality, and decline of cognitive indicators. Premorbid disorders in 56.2% of cases were preceded by clinical features of endogenous mental disorders such as a progressive or continuous-attack-like progressive course, low severity of positive symptoms in period of manifestation.